Impact of ferric carboxymaltose for iron deficiency at discharge after heart failure hospitalization: a European multinational economic evaluation. (7th March 2023) - McEwan, Phil; Harrison, Cale; Binnie, Rhona; Lewis, Ruth D.; Cohen‐Solal, Alain; Lund, Lars H.; Ohlsson, Marcus; von Haehling, Stephan; Comin‐Colet, Josep; Pascual‐Figal, Domingo A.; Wächter, Sandra; Dorigotti, Fabio; et al.
Abstract: Aims: Iron deficiency (ID) is comorbid in up to 50% patients with heart failure (HF) and exacerbates disease burden. Ferric carboxymaltose (FCM) reduced HF hospitalizations and improved quality of life when used to treat ID at discharge in patients hospitalized for acute HF with left ventricular ejection fraction <50% in the AFFIRM‐AHF trial. We quantified the effect of FCM on burden of disease and the wider pharmacoeconomic implications in France, Germany, Poland, Spain and Sweden. Methods and results: The per country eligible population was calculated, aligning with the 2021 European Society of Cardiology (ESC) HF guidelines and the AFFIRM‐AHF trial. Changes in burden of disease with FCM versus standard of care (SoC) were represented by disability‐adjusted life years (DALYs), hospitalization episodes and bed days, using AFFIRM‐AHF data. A Markov model was adapted to each country to estimate cost‐effectiveness and combined with epidemiology data to calculate the impact on healthcare budgets. Between 335 (Sweden) and 13 237 (Germany) DALYs were predicted to be avoided with FCM use annually. Fewer hospitalizations and shorter lengths of stay associated with FCM compared to SoC were projected to result in substantial annual savings in bed days, from 5215 in Sweden to 205 630 in Germany. In all countries, FCM was predicted to be dominant (cost saving with gains in quality‐adjusted life years), resulting in net savings to healthcare budgets within 1 year. Conclusions: This comprehensive evaluation of FCM therapy highlights the potential benefits that could be realized through implementation of the ESC HF guideline recommendations regarding ID treatment. Abstract : Methods used to capture the burden of disease and pharmacoeconomic evaluation of ferric carboxymaltose (FCM). AHF, acute heart failure; ID, iron deficiency; HF, heart failure; LVEF, left ventricular ejection fraction; SoC, standard of care.